KEANEKARAGAMAN ANGGREK EPIFIT DI KAWASAN TAMAN WISATA ALAM DANAU BUYAN-TAMBLINGAN - Pradnya Paramitha, I Gusti Ayu Agung; Ardhana, I Gede Putu; Pharmawati, Made (Metamorfosa: Journal of Biological Sciences, 2013)
Orchids are often found growing naturally in the tropical rain forest. Destruction of tropical rain forests can reduce the germplasms of natural orchids. One of the tropical rain forest areas which is often visited by tourists in Bali is Buyan-Tamblingan Nature Tourism Park. Research conducted from December 2011 until April 2012. The results showed that in the Buyan-Tamblingan Nature Tourism Park there are 30 species of epiphyte orchids. The epiphyte orchids which have the highest individual number is Appendicula elegans Rchb. f with total individual number was 198 individuals/ha. The Shannon-Wienner diversity index value of epiphyte orchid in Buyan-Tamblingan Nature Tourism Park is 1,1561.
Keywords: Diversity, epiphytic orchids, Buyan-Tamblingan Nature Tourism Park.